2017
DOI: 10.1128/aem.02924-16
|View full text |Cite
|
Sign up to set email alerts
|

Erg4A and Erg4B Are Required for Conidiation and Azole Resistance via Regulation of Ergosterol Biosynthesis in Aspergillus fumigatus

Abstract: Ergosterol, a fungus-specific sterol enriched in cell plasma membranes, is an effective antifungal drug target. However, current knowledge of the ergosterol biosynthesis process in the saprophytic human fungal pathogen Aspergillus fumigatus remains limited. In this study, we found that two endoplasmic reticulumlocalized sterol C-24 reductases encoded by both erg4A and erg4B homologs are required to catalyze the reaction during the final step of ergosterol biosynthesis. Loss of one homolog of Erg4 induces the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 43 publications
(35 reference statements)
8
26
0
Order By: Relevance
“…5B, the ROS level in P alcA ::erg10A mutant was significantly higher than in the WT (P Ͻ 0.001) in repression medium, whereas no difference was observed in inducing medium, suggesting that higher intercellular ROS level in P alcA ::erg10A mutant may account for the increased sensitivity toward oxidative stresses. Previous study has shown that sterol C-24 reductase ERG4A/B is involved in cell wall integrity in A. fumigatus (36). Similarly, as shown in Fig.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…5B, the ROS level in P alcA ::erg10A mutant was significantly higher than in the WT (P Ͻ 0.001) in repression medium, whereas no difference was observed in inducing medium, suggesting that higher intercellular ROS level in P alcA ::erg10A mutant may account for the increased sensitivity toward oxidative stresses. Previous study has shown that sterol C-24 reductase ERG4A/B is involved in cell wall integrity in A. fumigatus (36). Similarly, as shown in Fig.…”
Section: Resultssupporting
confidence: 69%
“…Indeed, widely used antifungal drugs such as azoles, allylamines, and polyenes target ergosterol and its biosynthesis. Of the approximately 20 enzymes involved in ergosterol synthesis, only ERG3 (C-5 sterol desaturase), ERG4 (C-24 sterol reductase), ERG11 (lanosterol 14-␣-demethylase), and ERG25 (C-4 methyl sterol oxidase) have been genetically characterized in the human opportunistic pathogen A. fumigatus (27,36,40,41). The physiological functions of the other enzymes involved in ergosterol biosynthesis are yet to be explored, including acetyl-CoA acetyl- on August 5, 2020 by guest http://aem.asm.org/ transferase ERG10, which is the initial enzyme in the mevalonate and ergosterol biosynthesis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, A. fumigatus is thermotolerant and can survive on a broad range of environmental niches (Haines, 1995;Seyedmousavi et al, 2015). Notably, it is one of the most prevalent airborne fungal pathogens, causing severe (usually fatal) invasive aspergillosis in immune compromised individuals (Ellett, Jorgensen, Frydman, Jones, & Irimia, 2017;Hillmann et al, 2015;Long, Xu, Zeng, Sang, & Lu, 2017;Throckmorton, Lim, Kontoyiannis, Zheng, & Keller, 2016). It has been identified that the virulence determinants of A. fumigatus are dependent on both fungal biological characteristics and host immune status (Cai et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Azoles, the first-line-used antifungals in clinic due to their limited side effects, damage the cell membrane through preventing the synthesis of ergosterol, a key component of fungal plasma membranes. Moreover, ergosterols are special lipids located in the cell membrane, which can regulate membrane fluidity and permeability (Bard et al, 1993;Kodedova & Sychrova, 2015;Long, Xu, Zeng, Sang, & Lu, 2017). It has been reported that sterols, along with sphingolipids, form membrane outer niches to support conformational functions of membrane proteins as well as serve as a platform for establishment of signalling molecules (Hinrichs, Klappe, Hummel, & Kok, 2004;Mongrand et al, 2004;Pasrija, Prasad, & Prasad, 2005).…”
mentioning
confidence: 99%